PENERAPAN STRATEGI 4P DALAM PEMASARAN PRODUK BAGRIK CRAFT - Selviana Rosinta Sari; Muhammad Anas (Universitas Muhammadiyah Surakarta, 2025)
The product produced by the Independent Entrepreneur Bagrik Craft is a business that has very good and profitable prospects. This is because the handicraft canvas fabric bag combined with lurik patchwork is a bag that raises the local culture of Indonesia. This study aims to analyze the 4P marketing strategy (Product, Price, Promotion, and Place) in order to find out marketing improvement efforts at BagrikCraft and to analyze the sales prospects of Bagrik Craft, seen from the profits earned during the research period. The research method used is to analyze marketing strategies and income and expenses in the production of Bagrik Craft handicraft bags during the period 4 November to 3December 2023. The results showed that the 4P marketing strategy was very influential on the level of sales of BagrikCraft products, and during the research period Bagrik Craft products sold as many as 100 units of bags with unit prices ranging from Rp55,000 to Rp65,000. Based on simple profit-loss calculations, it can be said to be profitable with the income obtained, namely Rp6,020,000 > Rp5,000,000.